Maternal mortality in Peru in the context of the COVID-19 pandemic - Chipa Avila, Mishel Rocio (2023)
Mr. EditorDuring the pandemic, the maternal mortality rate has increased, especially in underdeveloped countries, where one in three pregnant women with COVID-19 could not access the intensive care unit (ICU); therefore, 35% of pregnant women died and the measures to prevent COVID-19 infection had an impact in limiting the complete control of pregnant women (1). This pandemic had a significant impact on maternal mortality worldwide. In some countries there was an increase in the maternal mortality rate, such as Uganda with 6.5%, Mexico 26.2%, India 34.4% and Kenya 8.5% (2). In Latin America, Honduras had the highest mortality rate, while Peru was in fifth place, with a 50% increase (3). In Peru, maternal mortality had an unequal presence, according to the region, since before the pandemic, the regions that reported the highest mortality rates were Amazonas, Ucayali, Madre de Dios and Loreto; while during the pandemic, the departments that reported the highest incidence of maternal mortality were Lima, La Libertad, Piura, Cajamarca, Puno, which together accounted for 65.8% of all deaths during this time (4). On the other hand, the main change in the causes of maternal mortality as a result of the COVID-19 pandemic was the gradual rise of indirect causes such as respiratory diseases, COVID-19, among others; displacing direct causes such as hypertensive disorders and obstetric hemorrhage, which before the pandemic were the predominant causes at the national level (5). However, during the first months of 2022, 68.3% of the total maternal mortality occurred due to direct causes and 31.7% due to indirect causes, with similarities observed from the second semester of 2021 (6). In conclusion, since maternal mortality represents a serious public health problem, it is of interest to know aspects related to maternal mortality in Peru, which occurred in the context of the COVID-19 pandemic, and to use these experiences in future similar scenarios where the public health of pregnant women is involved.